Legal Certainty of Digital Assets Non-Fungible Token (NFT) on The Opensea Platform - Ulfanora Ulfanora; Almaududi Almaududi (LPPM Universitas Ekasakti Padang, 2023)
The role of technology in everyday life has become more sufficient. This technology results in digitalization which gives rise to digital assets that later become crypto assets that use blockchain technology to store data. The development of these crypto assets presents a technology called Non-Fungible Token (NFT) which is a technology linked to a work of art or other digital assets that serves to protect the artwork or digital assets and as proof of ownership. NFT presents a new way for artists to sell their art more safely and avoid harmful actions. However, the widespread use of NFT technology has created a problem due to the lack of legality regarding NFT. The formulation of the problems discussed in this thesis are: 1. What is the legal certainty for digital assets in the form of Non-Fungible Tokens (NFT) on the Opensea digital platform? 2. What is the legality of Smart Contracts in each transaction of Non-Fungible Token (NFT) through the Opensea digital platform? The research method used is a normative juridical research method, taking a statutory approach and having a descriptive-analytical nature. From the results of this research, can be seen that NFT has not been clearly regulated in Indonesian positive law, resulting in a legal vacuum. Regulations regarding Crypto are regulated by Bappebti as the governing body. Bappebti itself has not specifically regulated NFT regulations in Bappebti regulations. Besides that, other arrangements are seen through the Civil Code which regulates NFT as an intangible object ITE Law which regulates the implementation of the transaction. And regarding the protection of its Intelectual Property Rights through the Copyright Law. Then regarding the validity of the Smart Contract in Non-Fungible Token (NFT) transactions it is considered valid in Indonesian positive law based on the Pacta sunt servanda principle and must be based on the compliance of Article 1320 of the Civil Code.